PHARMACOEPIDEMIOLOGY IN THE ASSORTMENT POLICY-PRODUCER OF DRUGS - V. Y. Krasnov (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2015)
RETRACTED ARTICLEThe analysis of the range of the medicines presented by the pharmaceutical company «Servier » in the Russian market, applied is carried out at treatment of a wide range of diseases. The expert assessment of a pharmacoepidemiology approach is carried out during the developing, introduction and a promotion of medi-cines. Adaptation of innovative methods of formation of product range and the range taking into account a pharmacoepidemiology for domestic pharmaceutical companies is made.